2011
DOI: 10.1177/0148607111415530
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Effects of a Subcutaneous Injection of Sesame Oil Against Iron‐Induced Acute Renal Injury in Mice

Abstract: Background: Iron intoxication causes acute nephrotoxicity in animals and humans. Sesame oil, a healthful food, increases resistance to lipid peroxidation and protects against multiple organ injury in various animal models. The authors examined the prophylactic and therapeutic effects of a subcutaneous injection of sesame oil against iron‐induced acute renal injury in mice. Methods: Iron intoxication in mice was induced with an intraperitoneal injection (2 mg/kg) of ferric‐nitrilotriacetate (Fe‐NTA). Various do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Sesame oil and sesamol may be alternative approaches for managing metal intoxication. They are potent for treating metal‐associated toxicity 58 , 69 , 73 , 74 , 76 . In addition, sesamol significantly inhibits the iron‐mediated Haber‐Weiss reaction 78 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sesame oil and sesamol may be alternative approaches for managing metal intoxication. They are potent for treating metal‐associated toxicity 58 , 69 , 73 , 74 , 76 . In addition, sesamol significantly inhibits the iron‐mediated Haber‐Weiss reaction 78 .…”
Section: Resultsmentioning
confidence: 99%
“…In sesame's long history as a crop and oil, no harmful effects of sesame seed extracts have been reported. Sesame oil and sesamol show no observable adverse effects in treating lead and iron intoxication in rats 58 , 66 , 70 , 73 76 . Because metal chelating therapy is associated with adverse effects, treating heavy metal toxicity in addition with sesame oil and sesamol may be better alternatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, low serum K + and high urinary K + suggest that the potassium in blood may be overexcreted in DOCA/salt‐induced hypertensive rats 4 , 5 . Our previous studies have shown both protective and therapeutic effects of sesame oil on kidney damage and cardiac injury upon insults 36 , 37 . In the present study, the cardiac hypertrophy may have been induced by the persistent hypertension, which in turn deteriorated cardiac function and ultimately led to a failing heart 38 , 39 .…”
Section: Discussionmentioning
confidence: 96%